2021
DOI: 10.3390/nu13124191
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 3′Sialyllactose-Poor Milk during Lactation Impairs Cognitive Capabilities in Adulthood

Abstract: Breast milk exerts pivotal regulatory functions early in development whereby it contributes to the maturation of brain and associated cognitive functions. However, the specific components of maternal milk mediating this process have remained elusive. Sialylated human milk oligosaccharides (HMOs) represent likely candidates since they constitute the principal neonatal dietary source of sialic acid, which is crucial for brain development and neuronal patterning. We hypothesize that the selective neonatal lactati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 61 publications
4
18
0
Order By: Relevance
“…Our data show that WT mice reared with a reduction of 3 SL and an absence of 6 SL exhibited, in adulthood, reduced spatial, working and recognition memory compared to WT mice receiving normal milk. These findings confirm our previous studies evaluating the effect of the lack of 6 SL and reduction of 3 SL alone on memory capabilities (Hauser et al, 2021;Pisa et al, 2021). Furthermore, this result is also in agreement with other studies that reported beneficial effects of dietary supplementation of sialic acid in piglets (Wang et al, 2007) and sialylated oligosaccharides in preterm pigs (Obelitz-Ryom et al, 2019) and mice (Tarr et al, 2015).…”
Section: Selective Deprivation Of 3 Sl and 6 Sl Impaired Memory And A...supporting
confidence: 93%
See 1 more Smart Citation
“…Our data show that WT mice reared with a reduction of 3 SL and an absence of 6 SL exhibited, in adulthood, reduced spatial, working and recognition memory compared to WT mice receiving normal milk. These findings confirm our previous studies evaluating the effect of the lack of 6 SL and reduction of 3 SL alone on memory capabilities (Hauser et al, 2021;Pisa et al, 2021). Furthermore, this result is also in agreement with other studies that reported beneficial effects of dietary supplementation of sialic acid in piglets (Wang et al, 2007) and sialylated oligosaccharides in preterm pigs (Obelitz-Ryom et al, 2019) and mice (Tarr et al, 2015).…”
Section: Selective Deprivation Of 3 Sl and 6 Sl Impaired Memory And A...supporting
confidence: 93%
“…Adult WT and heterozygous (HZ) B6.129-St6gal1 tm2Jxm /J and HZ B6.129-St3gal4 tm1.1Jxm /J were purchased from a commercial breeder (the Jackson Laboratory, Bar Harbor, ME, USA). Then, homozygous knock-out (KO-ST3) B6.129-St3gal4 tm1.1Jxm / tm1.1Jxm and homozygous knock-out (KO-ST6) B6.129-St6gal1 tm2Jxm / tm2Jxm were derived from heterozygous St3gal4 B6.129-St3gal4 tm1.1Jxm /J 10.3389/fncel.2023.1091890 and St6gal1 B6.129-St6gal1 tm2Jxm /J mice [as described in Pisa et al (2021) and Hauser et al (2021), respectively]. Mice were housed in same-sex groups of 2-3 animals, in type-1 polycarbonate cages (33.0 × 13.0 × 14.0 cm) equipped with sawdust bedding, an enrichment bag (Mucedola, Settimo Milanese, Italy), metal top and ad libitum water and food pellets (Mucedola, Settimo Milanese, Italy).…”
Section: Animals and Rearing Conditionsmentioning
confidence: 99%
“…In both term and preterm infants, human milk feeding is associated with improved neurodevelopmental outcomes [ 157 , 158 ]. This has been partially attributed to hMOS, including 2’FL, 3’-sialyllactose (3’SL) and 6’-sialyllactose (6’SL), for their contribution to synaptic formation, neuro-transmission, and memory improvement [ 159 , 160 , 161 , 162 , 163 , 164 , 165 ]. HMEV-derived miR-148a-3p may work in concert with hMOS and other human milk components on brain development during infancy.…”
Section: Biology Of Hmevsmentioning
confidence: 99%
“…On the other hand, 3-fucosyllactose, lacto-N-neotetraose and lactodifucotetraose reduce inflammation by blocking the activation of TNF-α [ 28 ]. Sialyated HMOs have been described to increase host susceptibility to colitis [ 50 ] and improve cognitive function in vivo [ 51 ].…”
Section: Discussionmentioning
confidence: 99%